Strategy Public Sector Leadership dalam Peningkatan Kualitas Pelayanan pada Dinas Pemberdayaan Masyarakat dan Desa Provinsi Sulawesi Tengah - Rezka Fahmi Tiara; Muhammad Khairil; Ani Susanti (Transgenera: Jurnal Sosial, Politik dan Humaniora, 2025)
This research examines the implementation of public sector leadership strategies in improving service quality at the Department of Community and Village Empowerment of Central Sulawesi Province. Using Van Wart's (2003) theoretical framework, this research analyzes three main dimensions: skills, traits, and leadership styles. Through qualitative methods including in-depth interviews with key informants and document analysis, the research reveals that effective public sector leadership requires a balanced integration between technical competencies, personal characteristics, and adaptive leadership approaches. The findings show that participative and transformational leadership styles, combined with strong technical skills and ethical traits, contribute significantly to improving public service quality